CULTURAL MEMORY: AN ANALYSIS OF MYTHS AND BELIEFS IN AMINATTA FORNA’S ANCESTOR STONES - K, Monisha; Sreelatha, S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
African countries are known for their multilayered cultures and practices. The African continent, which is addressed as a tribal continent of 54 countries which are divided as North Africa, Central or Middle Africa, South Africa, East Africa and West Africa. Each African country is unique in following and practicing their own traditional rules and customs. African people have different kinds of beliefs and lifestyles which are connected with cultural memory. Cultural memory explores how memory is formulated, portrayed, and implemented through cultural practices, ceremonies, narratives, and signs. Aminatta Forna’s Ancestor Stones (2006) highlights the lifestyle of a particular community of Rofthane village from West Africa. West Africa is known for its folktales, which are shared by the people from generation to generation. The folktales are known them as stories and myths which are the cultural part of their society. In the novel, Aminatta Forna highlights the storytelling of real-life incidents by exposing the rituals, traditional practices, and customs. The author, through her debut fiction, Ancestor Stones showcases the life style rituals of the Rofthane by focusing on the family of the village head Gibril Umaru Kholifa. Though she shares the story of a particular family, it covers the history of the whole families of African society. The novel revolves around the memories of four protagonists, who are sharing their experiences to their niece, Abie. The paper not only showcases the traditional customs and myths of African people but also their anxiety and sufferings, and the cultural evolution from the memories of different generations.